Case–control study of low-back pain referred for magnetic resonance imaging, with special focus on whole-body vibration - Palmer, Keith T.; Harris, E. Clare; Griffin, Michael J.; Bennett, James; Reading, Isabel; Sampson, Madeleine; Coggon, David (Scandinavian Journal of Work, Environment & Health, 2008)
' ' OBJECTIVES ': 'This study investigated risk factors for low-back pain among patients referred for magnetic resonance imaging (MRI), with special focus on whole-body vibration. ' ' METHODS ': 'A case–control approach was used. The study population comprised working-aged persons from a catchment area for radiology services. The cases were those in a consecutive series referred for a lumbar MRI because of low-back pain. The controls were age- and gender-matched persons X-rayed for other reasons. Altogether, 252 cases and 820 controls were studied, including 185 professional drivers. The participants were questioned about physical factors loading the spine, psychosocial factors, driving, personal characteristics, mental health, and certain beliefs about low-back pain. Exposure to whole-body vibration was assessed by six measures, including weekly duration of professional driving, hours driven in one period, and current root mean square A(8). Associations with whole-body vibration were examined with adjustment for age, gender, and other potential confounders. ' ' RESULTS ': 'Strong associations were found with poor mental health and belief in work as a causal factor for low-back pain, and with occupational sitting for ≥3 hours while not driving. Associations were also found for taller stature, consulting propensity, body mass index, smoking history, fear–avoidance beliefs, frequent twisting, low decision latitude, and low support at work. However, the associations with the six metrics of whole-body vibration were weak and not statistically significant, and no exposure–response relationships were found. ' ' CONCLUSIONS ': 'Little evidence of a risk from professional driving or whole-body vibration was found. Drivers were substantially less heavily exposed to whole-body vibration than in some earlier surveys. Nonetheless, it seems that, at the population level, whole-body vibration is not an important cause of low-back pain among those referred for MRI.
Keywords: back; back pain; case–control study; driving; imaging; low back; low-back pain; magnetic resonance imaging; mental health; MRI; occupational risk factor; radiology; risk factor; vibration; whole-body vibration